NOD2 in monocytes negatively regulates macrophage development through TNFalpha - Chauvin, Camille; Alvarez-Simon, Daniel; Radulovic, Katarina; Boulard, Olivier; Laine, William; Delacre, Myriam; Waldschmitt, Nadine; Segura, Elodie; Kluza, Jérome; Chamaillard, Mathias; Poulin, Lionel F. (Frontiers in Immunology, 2023)
Objective It is believed that intestinal recruitment of monocytes from Crohn’s Disease (CD) patients who carry NOD2 risk alleles may repeatedly give rise to recruitment of pathogenic macrophages. We investigated an alternative possibility that NOD2 may rather inhibit their differentiation from intravasating monocytes. Design The monocyte fate decision was examined by using germ-free mice, mixed bone marrow chimeras and a culture system yielding macrophages and monocyte-derived dendritic cells (mo-DCs). Results We observed a decrease in the frequency of mo-DCs in the colon of Nod2-deficient mice, despite a similar abundance of monocytes. This decrease was independent of the changes in the gut microbiota and dysbiosis caused by Nod2 deficiency. Similarly, the pool of mo-DCs was poorly reconstituted in a Nod2-deficient mixed bone marrow (BM) chimera. The use of pharmacological inhibitors revealed that activation of NOD2 during monocyte-derived cell development, dominantly inhibits mTOR-mediated macrophage differentiation in a TNFα-dependent manner. These observations were supported by the identification of a TNFα-dependent response to muramyl dipeptide (MDP) that is specifically lost when CD14-expressing blood cells bear a frameshift mutation in NOD2. Conclusion NOD2 negatively regulates a macrophage developmental program through a feed-forward loop that could be exploited for overcoming resistance to anti-TNF therapy in CD.